Comprehensive thermal resistance model of forced air cooling system for multiple power chips. (April 2021) - Lin, Hongyi; Guo, Xiao; Chen, Guozhu
Abstract: It is necessary to design a heat sink according to the losses of chips in the application of power chips to maintain the temperature of the chip junction at a low level. Since multiple power chips are distributed on the same heat sink, the surface temperature of the heat sink is unevenly distributed, the chips located at the air outlet need to withstand higher temperatures. In order to describe the surface temperature of the heat sink accurately, a novel comprehensive thermal resistance of the forced air cooling system for multi-power chips was proposed. A temperature rise test by a static var generator (SVG) prototype was designed to prove the accuracy of the model proposed. The thermal resistance error of the model proposed in this paper is only 2%. Comparing with two traditional thermal models, the accuracy of the novel thermal resistance model is improved by more than 20%.